PENGARUH PENDIDIKAN KESEHATAN TENTANG PERTOLONGAN PERTAMA PADA SPRAIN DENGAN MEDIA AUDIOVISUAL TERHADAP TINGKAT PENGETAHUAN PEMAIN FUTSAL DI SURAKARTA - Gatot Suparmanto; Ratih Dwilestari; Nadia Sefani (Sekolah Tinggi Ilmu Kesehatan Rajawali, 2022)
Sprain are acute injuries that occur to the ligaments. Therefore, there is a requirement for health education by performing appropriate first aid using the audiovisual method. An educational media uses the senses of hearing and sight to facilitate the delivery of exciting material. This study adopted a quasi-experiment with one group pre-test and post-test without control design. The sampling technique was non-probability sampling with the total sampling technique of 20 futsal players. Respondents' knowledge of Sprain first aid in the pre-intervention was in the poor category with 11 respondents (55%). In the post-intervention, 17 respondents (85%) had good knowledge of Sprain first aid. The Wilcoxon test results presented the knowledge level of Sprain first aid in futsal players with p-value = 0.000 (p-value <0.05). Therefore, there was an effect of health education about Sprain first aid with audiovisual media on the knowledge level of futsal players in Surakarta. .